Optimasi Rute Distribusi Logistik pada Bekangdam dengan Algoritma Bee Colony - Nadiah Nur Fadillah Ramadhani; Bayu Rahayudi; Imam Cholissodin (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2021)
Kodam V Brawijaya is the Regional Defense Command in East Java Province. The area of ​​Kodam V Brawijaya covers areas spread across East Java such as Pacitan, Ngawi, Madiun, Blitar, Nganjuk, Kediri, Mojokerto, Malang, Situbondo to Banyuwangi. One of the bodies in Kodam V Brawijaya is Bekangdam. Bekangdam or Kodam Transport Provisions is the regional implementing agency of the Indonesian Army in the regions whose function is to provide supplies for combat logistics and war transportation. The supplies for Bekangdam will be distributed to the areas of Kodam V Brawijaya. In addition to combat equipment and war transportation, Bekangdam's logistics are in the form of food, medicine and other basic materials. The distribution process at Bekangdam uses land transportation in the form of trucks. Bekangdam has obstacles in determining the optimal route because of that in the delivery process Bekangdam often experiences delays. Based on these problems, an appropriate method is needed to deal with this problem, this study uses the bee colony algorithm in solving the case of multiple traveling salesman problems with the aim of finding the optimal route in the logistics distribution process. Based on the tests carried out, the route generated by the system is more optimal than the route chosen by Bekangdam V Brawijaya. This study obtained the optimal value for the 115th popsize, the 40th limit and the 1200th iteration. From the parameters used, the total distance from the system was 2454.65 km, while the total distance selected by Bekangdam was 2874.1 km.